Key concepts in muscle regeneration: muscle "cellular ecology" integrates a gestalt of cellular cross-talk, motility, and activity to remodel structure and restore function - Anderson, J. E. (European Journal of Applied Physiology, 2022)
This review identifies some key concepts of muscle regeneration, viewed from perspectives of classical and modern research. Early insights noted the pattern and sequence of regeneration across species was similar, regardless of the type of injury, and differed from epimorphic limb regeneration. While potential benefits of exercise for tissue repair was debated, regeneration was not presumed to deliver functional restoration, especially after ischemia-reperfusion injury; muscle could develop fibrosis and ectopic bone and fat. Standard protocols and tools were identified as necessary for tracking injury and outcomes. Current concepts vastly extend early insights. Myogenic regeneration occurs within the environment of muscle tissue. Intercellular cross-talk generates an interactive system of cellular networks that with the extracellular matrix and local, regional, and systemic influences, forms the larger gestalt of the satellite cell niche. Regenerative potential and adaptive plasticity are overlain by epigenetically regionalized responsiveness and contributions by myogenic, endothelial, and fibroadipogenic progenitors and inflammatory and metabolic processes. Muscle architecture is a living portrait of functional regulatory hierarchies, while cellular dynamics, physical activity, and muscle-tendon-bone biomechanics arbitrate regeneration. The scope of ongoing research—from molecules and exosomes to morphology and physiology—reveals compelling new concepts in muscle regeneration that will guide future discoveries for use in application to fitness, rehabilitation, and disease prevention and treatment.